2011
DOI: 10.1111/j.1365-2036.2011.04809.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of functional constipation and comparison with constipation-predominant irritable bowel syndrome: the Systematic Investigation of Gastrointestinal Diseases in China (SILC)

Abstract: SUMMARY BackgroundThe epidemiology and effects of functional constipation (FC) on Chinese people remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 38 publications
4
60
2
2
Order By: Relevance
“…Our results were in agreement to the previous cross-sectional survey conducted in adult Chinese population (n = 16 078) where BMI, alcohol consumption, and smoking status were comparable across both constipation subtypes. 21 In 2008, Pourhoseingholi et al conducted a cross-sectional study in Tehran province where 40% of FC patients were overweight and 20% were obese, indicating a clear association between obesity and FC; however Zhao et al, in 2011 found a negative correlation between high BMI and FC and few studies reported no significant relationship between BMI and FC. [22][23][24] In 2013, Farzaneh et al evaluated the effects of demographic factors, BMI, alcohol drinking and smoking habits in 153 IBS patients against 163 non-IBS patients at Taleghani Hospital Gastroenterology Clinic at Tehran.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results were in agreement to the previous cross-sectional survey conducted in adult Chinese population (n = 16 078) where BMI, alcohol consumption, and smoking status were comparable across both constipation subtypes. 21 In 2008, Pourhoseingholi et al conducted a cross-sectional study in Tehran province where 40% of FC patients were overweight and 20% were obese, indicating a clear association between obesity and FC; however Zhao et al, in 2011 found a negative correlation between high BMI and FC and few studies reported no significant relationship between BMI and FC. [22][23][24] In 2013, Farzaneh et al evaluated the effects of demographic factors, BMI, alcohol drinking and smoking habits in 153 IBS patients against 163 non-IBS patients at Taleghani Hospital Gastroenterology Clinic at Tehran.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were comparable to a previously reported literature where patients with IBS-C were much more likely to report gastroesophageal reflux disorder. 21,39 In another study, dyspepsia and diabetes were reported as the most common comorbidities in patients with IBS-C and FC, respectively. 37 In addition, 7.15% patients of FC were on antidepressants for management of stress/ anxiety/ depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Some authors questioned the partitioning and treated the FC and IBS-C as distinct parts of a continuum, with differences based only on symptom severity. [4][5][6][7][8] Nevertheless, differential responses to treatment seem to suggest that FC and IBS-C may be different disorders. 9 Whether being different points of the same disorders or distinct disorders, it is of great importance in illustrating pathophysiological mechanisms underlying the discrimination between FC and IBS-C.…”
Section: Introductionmentioning
confidence: 99%
“…2 On the mainland of China, about 6% of population experience constipation, of which women and the elderly are the largest group. 3 Although non-life-threatening, long-term constipation can cause serious complications, such as diverticulosis of the colon, crissum diseases, and melanosis coli. 4 As Rogers concluded, chronic constipation not only can bring about discomfort but also affects a person's physical and psychological wellbeing, with further consequences of reduced quality of life and high costs for both families and society.…”
Section: Introductionmentioning
confidence: 99%